Intervenção psicossocial com famílias de crianças obesas por meio do grupo multifamiliar: vivências e percepções dos participantes - Nogueira, Heron Flores (2017)
Childhood obesity has reached levels never seen in our history. The family environment is one of the factors that can contribute to the emergence and maintenance of obesity, on the other hand, the participation of families is also considered as fundamental in prevention and treatment. In the literature there is notably a shortage of studies that focus on this issue. The present research has as general objective to perform a psychosocial intervention with families of obese children and to investigate their experiences and perceptions about possible changes in family dynamics, eating habits and lifestyle. This is a qualitative research through action research from the perspective of the Systemic Approach to the Family. Three families with children diagnosed with obesity participated in this study, living in different administrative regions of the Federal District and having an average family income of two minimum wages. The instruments used for the collection were: family life cycle interview script, genogram, scripts for the Multifamily Group (MG), follow-up interview script, HAT-Helpful Aspects of Therapy and the CCI-Client Change Interview. After the signing of the Informed Consent Term, the families were interviewed separately and the genogram was built, with an average duration of two hours, at the UCB Applied Psychology Training Center (CEFPA). After a few weeks, in the same place, the families participated in the GM, which happened in five meetings, with biweekly intervals, each with an average duration of three hours. For these steps the researcher counted on scholarship students of Scientific Initiation of the course of Psychology. After two years, the families were interviewed by the researcher in their homes (follow-up) and each interview lasted an average of two hours. All stages of the research were recorded in audios, whose contents were later transcribed in full. The analysis of the information was made in the light of the Qualitative Epistemology in which the researcher realizes a constructive-interpretative production, and discussed based on the contribution of the systemic theory. The main aspects observed and discussed were organized in three stages: 1) the interview of the family life cycle: knowing the family and its history - the information collected showed the gestation of the babies without planning; Interaction pattern with conflicts, absence of parental authority and diffuse internal borders; Inadequate food pattern and difficulties in adhering to treatments. 2) The GM: interaction, learning and growth - transgenerational influences on the current food pattern and extensive family interferences; Difficulties in exercising the parental role and promoting adequate nutrition; Meanings of feeding and expression of intrafamilial affections; Attempts to make changes, and 3) the follow-up interview: revisiting families - jobs and activities remembered with ease; The changes made possible after the interventions; Current family dynamics with the presence of limits, authority and health care; Family contributions to the intervention model and expectations for the future. The present study, therefore, analyzed the families' experience in the psychosocial intervention, providing an in-depth and complex reading of the different factors related to childhood obesity and the family. This study can contribute to preventive actions and treatment of obesity, as well as help in the promotion of new research on the disease.